PORTABLE FINGERPRINT ATTENDANCE SYSTEM USING ARDUINO - TUNG, MUN THENG (Universiti Malaysia Sarawak (UNIMAS), 2020)
Currently, the generally utilized techniques for taking attendance in the class is by passing the paper sheet around for students to sign. This method comes out with a lot of problems, not only for students but also for lecturers. The proposed system aims to develop a portable attendance system that is used to take the attendance of students using their fingerprints. A web based system will be developed to help the lecturer more easily manage and keep track of the attendance records.